The use of interactive technologies in the formation of students' subjectivity: innovative practices - A. D. Kariyev; F. Orazbayeva; M. O. Iskakova; I. M. Dyussekeneva; M. Bakracheva (Russian State Vocational Pedagogical University, 2024)
Introduction. The development of human potential is an important direction of the state policy of the Republic of Kazakhstan in the field of ensuring the economic security of the country. In this regard, special attention is paid to the growth of human potential and its responsibility for the self-development and self-realisation of a new generation of citizens. Aim. The present research aimed to present innovative practices of the formation of students' subjectivity during the educational process through the use of special diagnostic and correctional-developmental tools. Methodology and research methods. The research was based on systemic, subjective, activity-based, and axiological approaches. The study extensively utilised methods for modelling the educational process. Results. It has been determined that the use of interactive technologies in the implementation of innovative practices contributes to the active formation of subjectivity of students during the educational process. Scientific novelty. Based on systemic, subjective, activity-based, and axiological approaches, the authors have developed a system for forming students' subjectivity during the educational process by actively utilising interactive technologies. Practical significance. The proposed system can be used by college and university teachers in practice to establish interaction with students.